Analisis Penerapan Konsep Value For Money Pada Pemerintah Kabupaten Bantul - Kurniawati, Nova; Adhivinna, Vidya Vitta (Universitas PGRI Yogyakarta, 2016)
The performance of The goverment institutions is now under the spotlight along with the improvement in public awareness on the course of general public administration.People are getting more and more intelligent and critical. They have demand for transparancy, clean, economical, effectual, responsive and accountable. The aim of this research is to discover the financial performance of Pemerintah Kabupaten Bantul during year 2010-2013. The test was done by using value for money method to measure the financial performance from the perspective of economy, effectiveness and efficiency which has shown in the annual budgetary report and realization from 2010-2013. The result from financial analysis on Pemerintah Kabupaten Bantul has shown that in economic perspective the financial management in Bantul can be said to be economical in year 2010 and getting better in 2011-2013. From effectiveness it can be said to be very effectual from 2010 till 2013, and from efficiency perspective Bantul Administration was not efficient in 2010, but in 2011 can be said to be very efficient and then in 2012-2013 can be said to be inefficient.